Tackling NCDs: The Need to Address Alcohol Industry Interference and Policy Incoherence Across Sectors; Comment on "Towards Preventing and Managing Conflict of Interest in Nutrition Policy? An Analysis of Submissions to a Consultation on a Draft WHO Tool" - Belinda Townsend; Mia Miller; Deborah Gleeson (Kerman University of Medical Sciences, 2022)
Ralston et al highlight the ways that different actors in global nutrition governance conceptualise and frame the role of non-state actors in governance arrangements, including the potential for conflict of interest (COI) to undermine global health efforts. The authors argue that the World Health Organization (WHO) draft tool on managing COI in nutrition policy is an important innovation in global health, but that further research and refinement is needed for operationalising the management of COI with diverse actors in diverse contexts. In this commentary, reflecting on strategic framing and industry interference in policy-making, we argue for the urgent need for states and intergovernmental organisations to prevent alcohol industry interference in the development of national and global alcohol policy. We argue that policy incoherence remains a key barrier, where governments pursue health goals in the health sector while pursuing exports and market liberalisation of health harmful commodities in the trade sector.